The Effect Of Self Regulated Learning On Learning Outcomes Through Learning Motivation In Class V In The Lituk Cluster, South Atambua District - Maxsel Koro; Hiwa Wonda; Maria Anjelina Ade Seran (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2022)
The purpose of this study is to (1) determine the effect of self-regulated learning on learning outcomes and (2) determine the effect of self-regulated learning on learning outcomes through student learning motivation in class V. This research is an associative research with quantitative research type, using a questionnaire path analysis model that used include The Motivated Strategies for Learning Questionnaire (MSLQ) developed by Pintrich and Groot (1990) to measure self-regulated learning and learning motivation. The results of the analysis show that: (1) There is a significant influence between self-regulated learning on student learning outcomes, seen from the two aspects of self-regulated learning indicators related to the use of cognitive strategies and self-regulation. (2) and there is a significant effect between self-regulated learning on student learning outcomes through learning motivation, seen from the three aspects related to self-efficacy, intrinsic value, and text anxiety.